Computer guided root tip extraction and implant placement: A clinical report - Jeong, Min; Kwon, David H.; Lee, Sang J. (The Journal of prosthetic dentistry, 2025)
Extraction of a residual root tip and implant placement can be challenging because of the complexity and invasiveness of the procedure. Improvised application of a guided implant surgery may avoid such challenges. This clinical report presents an innovative technique combining a 3-dimensionally printed surgical guide with conventional instrumentation for a residual root tip extraction in a minimally invasive and predictable way.